Convenient links for the estimation of hedonic price indexes - Ramalho, Esmeralda (2015)
Hedonic methods are a prominent approach in the construction of quality-adjusted price indexes. This paper shows that the process of computing such indexes is substantially simplified if arithmetic (geometric) price indexes are computed based on exponential (log-linear) hedonic functions estimated by the Poisson pseudomaximum likelihood (ordinary least squares) method. A Monte Carlo simulation study based on housing data illustrates the convenience of the links identified and the very attractive properties of the Poisson estimator in the hedonic framework.